On the uniqueness of a solution of the fourier problem for a system of sobolev-gal’pern type - Вas M. O.; Lavrenyuk, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We establish conditions for the uniqueness of a solution of the problem for a system of equations unresolved with respect to the time derivative without initial conditions in a noncylindrical domain. The system considered, in particular, contains pseudoparabolic equations.